EFFECTIVENESS OF HEALTH LITERACY PROGRAM FOR ERGONOMIC TO HEALTH BEHAVIOR OF DAIRY FARMERS IN TWO PROVINCES - วงษ์ศรี ภัทรภร; หีบแก้ว ปัดชาสุวรรณ์ นาฏนภา; คาวีวงศ์ ดุษฎี (Primary Health Care Journal (Northeastern Edition), 2026)
Musculoskeletal disorders (MSDs) are the leading health issue among continuous manual laborers, primarily stemming from poor workplace ergonomics. This quasi-experimental study aimed to investigate the effects of an ergonomic health literacy promotion program on the health behaviors of dairy farmers. The sample consisted of 60 dairy farmers, equally divided into an experimental group (n = 30) and a comparison group (n = 30). The experimental group participated in a 10-week ergonomic health literacy promotion program. Data were collected using questionnaires and working posture risk assessments, and subsequently analyzed utilizing descriptive and inferential statistics, specifically the Independent t-test and Paired t-test. The findings revealed that, post-intervention, the experimental group demonstrated a statistically significant increase in all five domains of ergonomic health literacy compared to both their pre-intervention baseline and the comparison group (p-value < 0.001). Furthermore, the experimental group exhibited significantly higher health behavior scores than the comparison group (Mean diff. = 32.57, 95% CI = 29.33 to 35.80, p-value < 0.001), along with a significant reduction in occupational risk (Mean diff. = -1.87, 95% CI = -2.38 to -1.35, p-value < 0.001). In conclusion, the ergonomic health literacy promotion program effectively enhances health behaviors and mitigates the risk of musculoskeletal disorders among dairy farmers. This program can serve as a practical guideline for addressing ergonomic challenges within the agricultural sector.